Student Hardiness Development Using Stress Inoculation Training-Based Group Counseling - Redi Eka Andriyanto; Muhammad Nurwahidin; Syarifuddin Dahlan (Sociometry Journal of Social Science, Art and Humanity, 2022)
Anyone can experience stressful conditions. The students are no exception when completing the final task (thesis). Students are required to be able to study independently with various targets that must be met through direct guidance from supervisors. The condition of students at this stage is vulnerable to various problems that can lead to stress conditions. This stress will be beneficial for students when they are well tolerated. However, not all students can tolerate the stress they experience. This is influenced by the level of hardiness possessed by each student. The importance of hardiness in its role in tolerating academic distress experienced by students in writing a thesis encourages educational practitioners, especially counselors, to provide counseling services that can touch on the hardiness aspect. The need for this service model encourages researchers to develop a model of group counseling services based on stress inoculation training in developing hardiness to increase students' academic distress tolerance in preparing a thesis. The development of this model will be carried out within three months by following the procedures in research and development (R&D). encourage researchers to develop a model of group counseling services based on stress inoculation training in developing hardiness to increase academic distress tolerance in students in preparing a thesis. The development of this model will be carried out within three months by following the procedures in research and development (R&D). encourage researchers to develop a model of group counseling services based on stress inoculation training in developing hardiness to increase academic distress tolerance in students in preparing a thesis. The development of this model will be carried out within three months by following the procedures in research and development (R&D).